2001
DOI: 10.1038/sj.bmt.1702788
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic recovery of ex vivo perfusion culture expanded bone marrow and unexpanded peripheral blood progenitors after myeloablative chemotherapy

Abstract: Ex vivo culture of hematopoietic progenitor cells for autologous transplantation has generated world-wide interest, since it offers the prospect of using a limited cell number, and may allow more efficient gene transfer and passive elimination of contaminating tumor cells. In this study, we expanded bone marrow (BM) cells from 10 breast cancer patients to determine whether small BM aliquots can durably restore hematopoiesis, and whether thrombopoietin (TPO) improves hematopoietic reconstitution after myeloabla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…When used as the sole source of hematopoietic support, this graft reconstituted neutrophil count after a median 16 (range 13-24) days and platelet count at a median of 24 (range 19-45) days. Engelhardt et al 46 found almost precisely the same results in a trial of similar design; neutrophil nadirs ranged from 9 to 18 (median 16) days and platelet nadirs spanned 16-49 (median 23) days. These findings are similar to unexpanded bone marrow, but slower than MPB.…”
Section: Clinical Trials Of Ex Vivo Expansionsupporting
confidence: 58%
See 1 more Smart Citation
“…When used as the sole source of hematopoietic support, this graft reconstituted neutrophil count after a median 16 (range 13-24) days and platelet count at a median of 24 (range 19-45) days. Engelhardt et al 46 found almost precisely the same results in a trial of similar design; neutrophil nadirs ranged from 9 to 18 (median 16) days and platelet nadirs spanned 16-49 (median 23) days. These findings are similar to unexpanded bone marrow, but slower than MPB.…”
Section: Clinical Trials Of Ex Vivo Expansionsupporting
confidence: 58%
“…2,45 Two groups of investigators began to incorporate the stromal components into the expansion cultures. 44,46 These two studies examined whether small aliquots of steady-state bone marrow can be harvested, expanded ex vivo, and used as the sole source to support hematopoietic recovery after high-dose chemotherapy. Both studies utilized a perfusion-based stromal cellcontaining expansion device that employed frequent medium, cytokine, and gas exchange.…”
Section: Clinical Trials Of Ex Vivo Expansionmentioning
confidence: 99%
“…This observation is in concordance with others showing that there is a strong inverse correlation between the expanded cell dose and the time to neutrophil or platelet recovery. [17][18][19] In our study, this correlation could explain the fact that, despite a short median date of platelet transfusion independence, all patients received at least one platelet transfusion. It could therefore be proposed to perform a future ex vivo expansion trial of MK progenitors by a combination of MGDF þ SCF after starting the culture with a much higher number of CD34 þ cells (45 Â 10 6 /kg) than that used in our study (1-2 Â 10 6 CD34 þ /kg).…”
Section: Discussionmentioning
confidence: 72%
“…5 Apart from cell surface markers for isolation of HSC, numerous other assays that measure the stem cell activity have been exploited. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Clonal analyses using limiting dilution assays in Dexter-like cultures have been used (quality analysis), however, these are time-consuming due to the number of flasks that have to be analyzed. 26,27 In the past, HSC have been characterized with respect to their ability to form spleen colonies in irradiated mice (CFU-S).…”
Section: Introductionmentioning
confidence: 99%